Study on determinants of employee engagement at Jabatan Kerja Raya Negeri Kelantan / Nur Damia Mohamad - Mohamad, Nur Damia (Faculty of Business and Management, 2018)
The purpose of this study is to determine the factors that influencing employee engagement. A sample of 155 respondents was selected through convenience sampling. Questionnaire was used as the instrument to collect response. Data has been collected at Jabatan Kerja Raya Negeri Kelantan. SPSS was used to analyse the data in order to get the final result of this research study. From the analysis conducted, result has proven that the dependent variable which is employee engagement had a significant correlation with independent variable which are working environment, leadership, and team & co-worker relationship. Working environment was identified as the most significance variables influencing employee engagement through the multiple regression analysis conducted.